Assessment of filter cake and biochar usage on soil attributes - Alves, Marcelo Rodrigo; Souza, Janardelly Gomes de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The aim of the present study was to evaluate the effect of different doses of filter cake and biochar on the chemical and biological attributes of the soil. Two experiments were set up, both in a completely randomized design, with 7 treatments and three replications, composed of: Experiment (SC) - soil without limestone + 1%, 2%, and 3% of filter cake (treatments SCTF1, SCTF2, and SCTF3, respectively) and, soil without limestone + 1%, 2%, and 3% of filter cake biochar (treatments SCBTF1, SCBTF2, and SCBTF3, respectively) plus the control treatment (TC); Experiment (CC) - soil with limestone + 1%, 2%, and 3% of filter cake (treatments CCTF1, CCTF2, and CCTF3, respectively) and, soil with limestone + 1%, 2%, and 3% of filter cake biochar (treatments CCBTF1, CCBTF2, and CCBTF3, respectively) plus the control treatment (TC). Subsequently, chemical (pH, OM, TOC, TN, P, K, Mg, Ca, Al, and H+Al) and biological (soil respiration, MBN, MBC, and dehydrogenase enzyme activity) analyses were performed. Variance and simple linear regression analyses (t-test at 5% probability) were conducted using the R software. For the comparison of means, the Scott-Knott test at 5% probability was used. The soil chemical attributes were influenced by the levels of TF and BTF, SC, and CC, showing higher values at the 3% level. For the biological attributes, SCTF3 was the most notable.
Keywords: Industrial Residue; Sugarcane; Pyrolysis; Soil Fertility